PENGARUH PARTISIPASI PEMAKAI SISTEM INFORMASI AKUNTANSI DAN KECANGGIHAN TEKNOLOGI INFORMASI TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI DENGAN KEMAMPUAN TEKNIK PERSONAL SEBAGAI VARIABEL PEMODERASI PADA LEMBAGA PERKREDITAN DESA DI KECAMATAN SUKAWATI - I Putu Deddy Samtika Putra; Sang Ayu Putu Arie Indraswarawati (Jurnal Widya Akuntansi dan Keuangan, 2020)
The accounting information system effectiveness is a success achieved by accounting information system in generating information in a timely and accurate. The success of accounting information system is supported by several factors, namely the user participation of accounting information system the technology sophistication information and personal technical capability. This study aims to determine the effect of user participation of accounting information system and the technology sophistication information to the accounting information system effectiveness with personal technical capability as variable of moderate. The research was conducted on the LPD in district Sukawati. The population in this research is all LPD employees in district Sukawati amounting to 267 employees from 33 LPD. The sampling technique used is the purposive sampling method, in order to obtain a sample of 111 people from 23 LPD. Data collection by using a survey method, wich is spread questionnaire. The analytical techniques used is Moderated Regression analysis (MRA). Based on the results of the hypothesis testing suggests that the user participation of accounting information system has no significant effect on the accounting information system effectiveness, with parameter coefficient value of 0.003 with significance of 0.986 > 0.05. The technology sophistication information positively and significantly affects the accounting information system effectiveness, with a parameter coefficient value of 0.452 with significance of 0.002 < 0.05. Personal technical capability does not moderate the influence of the user participation of accounting information system to the accounting information system effectiveness, with a parameter coefficient value of -0.004 with significance of 0.938 > 0.05. The ability of personal technical capability does not moderate the influence of the technology sophistication information to the accounting information system effectiveness, with a parameter coefficient value of -0.007 with significance of 0.893 > 0.05.